African Pentecostal Spirituality and Civic Engagement: The Case of the Redeemed Christian Church of God in Britain - Burgess, Richard (Journal of Beliefs & Values, 2009)
African Pentecostal churches are becoming increasingly important in Britain where they are growing at a time when mainstream Christianity is in decline. Originally functioning as social and religious support networks for African migrants, their growth has been stimulated by a conscious missionary agenda. Recently, there has been a shift towards a more holistic understanding of mission in some African churches, which includes social ministry and political action. The focus of this article is the Redeemed Christian Church of God (RCCG), a transnational Nigerian Pentecostal denomination with close to 400 congregations in Britain. It suggests that the RCCG’s social orientation has been influenced by its internal theology, its Pentecostal experience and its external social context. It explores the way it has articulated and implemented its social vision in a multicultural and fragmented society.
paid